PERILAKU PENCARIAN PENGOBATAN PADA WANITA DENGAN IVA (INSPEKSI VISUAL DENGAN ASAM ASETAT) POSITIFDI PUSKESMAS HALMAHERA DAN PUSKESMAS KEDUNGMUNDU KOTA SEMARANG - Isti Awalina Zulfa (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Cervical cancer is a type of cancer is the fourth most commonly found in women. In controlling cervical cancer, the Government have to give Visual Inspection with Acetic Acid (VIA) test for early detection of cervical cancer. Abnormal ephytelium cell will give a description of acetowhite that called positive VIA. During October 2014 until juni 2015 Public Health Center of Halmahera and Public Health Center of Kedungmundu found 45 womans with positive VIA but only 24 womans of that want to go to Hospital. This fact show that there are a minimum health seeking behavior at women with Positive VIA. The Goal of this research is analyze health seeking behavior at women with Positive VIA in Public Health Center of Halmahera and Public Health Center of Kedungmundu. This type of research is descriptive analytic with cross sectional approach. Sample of this research are 35 womans with Positive VIA in Public Health Center of Halmahera and Public Health Center of Kedungmundu. From this research, we can find that from 35 womans with Positive VIA in Public Health Center of Halmahera and Public Health Center of Kedungmundu there are 21 womans didn’t find a health seeking behavior. Data analysis using chi square with a 95% confidence level. Statistical analysis showed that the variables have a relationship with health seeking behavior of positive VIA is education of health employer (p-value = 0.023), and experience (p-value = 0.039). while for variables that do not have a relationship with the health seeking behavior positive VIA is the age (p-value = 1.000), educational level (p-value = 1.000), age of first married (p-value = 0.727), family history of cancer (p-value = 0,400), work ( p-value = 0.727), sallary (p-value = 0.830), knowledge (p-value = 0.439), perception of susceptibility (p-value = 0.617), perception of seriousness (p-value = 0.407), perceived benefits (p-value = 0.056), perceived barriers (p-value = 1.000) , access of media information (p-value = 0.296). Suggestions of health employer to increase the health promotion of VIA, positive VIA, and cervical cancer.